1995
DOI: 10.1203/00006450-199511000-00028
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Asphyxia on the Pharmacokinetics of Ceftazidime in the Term Newborn

Abstract: Vol. 38, No. 5, 1995 Printed ill U.S.A.ml.zh), CAZ clearance per kg (40.9 ± 6.1 mLih/kg versus 60.8 ± 8.3 mLih/kg), and the GFR expressed in mLimin (3.14 ± 0.43 versus 4.73 ± 0.89) were significantly (p < 0.001) decreased in the asphyxiated newborn. We conclud e that twice daily administration of 50 rug/kg of body weight CAZ given to asphyxiated term newborns in the first days of life results in significantly higher serum trough levels in comparison with control infants. The impaired CAZ clea rance is a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Probably, due to the background, some other reports also used a relatively small number (approximately 20 cases) of patients with asphyxia [23,40] .…”
Section: Discussionmentioning
confidence: 99%
“…Probably, due to the background, some other reports also used a relatively small number (approximately 20 cases) of patients with asphyxia [23,40] .…”
Section: Discussionmentioning
confidence: 99%
“…To further illustrate this, critical illness associated with inflammation results in down regulation of DMEs [27]. Perinatal asphyxia results in a decrease in renal function in neonates up to 40-50% [29,30]. Furthermore, the status of the ductus arteriosus (open/closed) has an impact on both clearance and volume of distribution.…”
Section: Changes In Drug Metabolism: Enzyme Maturation and Non-maturamentioning
confidence: 99%
“…In general, asphyxia may induce changes in drug disposition, such as reduced or altered drug absorption, increased or unchanged volume of distribution, and decreased drug clearance [ 173 , 174 ]. For example, the elimination of the serum half-life and serum trough concentrations of ceftazidime were significantly increased in asphyxiated neonates, whereas the clearance and GFR of ceftazidime decreased [ 175 ]. Another study based on a popPK model found that gentamicin clearance was significantly reduced in asphyxiated neonates compared to that in non-asphyxiated neonates, and a prolonged dosing interval was necessary to achieve target trough concentrations in this subpopulation [ 176 ].…”
Section: Resultsmentioning
confidence: 99%